Retificador SEPIC trifásico isolado operando em DCM para aplicação em aerogeradores de pequeno porte - Xavier, Milton Mariano (2022)
In the present work, an isolated SEPIC three-phase rectifier operating in DCM is proposed for small wind turbine applications. The proposed topology is attractive because of the low number of controlled semiconductors and, the fact that it operates in DCM, allows to obtain input currents with low THD, with a fixed duty cycle and without the use of current sensors. A study of steady-state operation is presented, which aims to find equations that allow the design of the components that make up the system. Additionally, control-oriented modeling is performed, where it is shown that only the output voltage control is needed. Finally, a 1kW prototype was built and tested with a conversion of 96 VCA to 400 VCC, where the experimental results obtained attest to the feasibility of the proposal for low power applications in wind turbines.